Internalization of Tolerance Values in Islamic Education - Puspo Nugroho (FITK UIN Walisongo, 2018)
The purpose of this paper is to know the internalization process of religious tolerance values such as tauhid, rahmah, musawah in educational institutions. This study took place in the SMP Muhammadiyah Salatiga, the Junior High School, which using a qualitative approach. The results of this study are that first, to put tolerance values into the curriculum, second, to develop vertical relationships in Allah SWT and horizontal fellow humans, third, to emphasize the implementation of tolerance values in the daily lives of students in realizing Islam rahmatan lil alamin, Fourth, the teacher gives examples of tolerance behavior in the learning process.AbstrakTujuan tulisan ini ingin mengetahui proses internallisasi nilai-nilai toleransi beragama seperti tauhid, rahmah, musawah di lembaga pendidikan. Penelitian ini mengambil lokasi di Sekolah Menengah Pertama Muhammadiyah Salatiga dengan menggunakan pendekatan kualitatif. Hasil penelitian ini adalah pertama memasukkan nilai-nilai toleransi ke dalam kurikulum, kedua : membangun hubungan vertikal pada Allah SWT dan horizontal sesama manusia, ketiga: menekankan pelaksanaan nilai-nilai toleransi dalam kehidupan sehari-hari siswa dalam mewujudkan Islam rahmatan lil alamin. Ke empat: guru memberi contoh prilaku toleransi dalam proses pembelajaran.